EVALUASI MANAJEMEN TERPADU BALITA SAKIT (MTBS) PADA BAYI BERAT LAHIR RENDAH (BBLR) DI PUSKESMAS KABUPATEN KUNINGAN - , Dewi Vimala ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: In the entire world, it is estimated four million babies die each year, 99% of whom occur in developing countries. In Kuningan District in 2009, 258 cases of infant deaths were found and, of the numbers, 51 infants died due to Low Birth Weight (LBW) (38.06%). Neonatal death can be prevented with an Integrated Management of Neonatal Childhood Illness (IMNCI). So in the 1996 the World Health Organization and UNICEF to develop a program of Integrated Management of Childhood Illness (IMCI) is an effort to address the infants and under-five morbidity and mortality, by integrating promotive, preventive and curative services in the five diseases (pneumonia, diarrhea, measles, malaria and malnutrition) as causes of death in infants and young children in developing countries. Objective: To evaluate human resources programs implementing IMCI in the management of LBW. Methods: It was an observational study with a cross-sectional study design quantitative and qualitative approaches. The study population was health providers. Data analysis was univariate, bivariate, and multivariate analyses and qualitative data from in-depth interviews. Results: Multivariate analysis showed that the more dominant variable in predicting the scope of IMCI was the education variable (PR 4.19 95% CI 1.44 to 12.16) followed by provider training (PR = 2.45 CI 95% = 1, 05 to 5.68), length of work (PR = 3.02 95% CI = 1.29 to 7.08) and facility (PR = 2.45 95% CI = 1.05 to 5.68). Health provider with high education tended to have the motivation and better work spirit. The existence of spirit could improve service delivery so that the scope of the program could be better achieved. Conclusion: Education factor of IMCI implementer was more dominant contributing to the coverage of IMCI program compared to the factors of provider training, length of work and facility.